2007
DOI: 10.1007/s10802-007-9140-5
|View full text |Cite
|
Sign up to set email alerts
|

Fundamental Movement Skills and Children with Attention-Deficit Hyperactivity Disorder: Peer Comparisons and Stimulant Effects

Abstract: The purpose of this study was to compare the fundamental movement skills of 22 children with attention-deficit hyperactivity disorder (ADHD), from 6 to 12 years of age, to gender- and age-matched peers without ADHD and assess the effects of stimulant medication on the movement skill performance of the children with ADHD. Repeated measures analyses revealed significant skill differences between children with and without ADHD (p Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
41
3
4

Year Published

2011
2011
2017
2017

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 66 publications
(54 citation statements)
references
References 53 publications
6
41
3
4
Order By: Relevance
“…Similarly, treatment with stimulant medication improved handwriting (Flapper et al 2006) and overall motor performance in children with ADHD and/or DCD on the Motor Assessment Battery for Children (MABC) (Flapper et al 2006;Bart et al 2010) and the Motor Function Neurological Assessment (MFNU) (Stray et al 2009b), although balance was not improved by stimulants (Bart et al 2006). Other studies similarly found that larger motor skills (as measured by the Test of Gross Motor Development-2) were less affected by stimulant medication treatment (Harvey et al 2007). …”
Section: Approaches To Motor Assessment In Adhdmentioning
confidence: 92%
“…Similarly, treatment with stimulant medication improved handwriting (Flapper et al 2006) and overall motor performance in children with ADHD and/or DCD on the Motor Assessment Battery for Children (MABC) (Flapper et al 2006;Bart et al 2010) and the Motor Function Neurological Assessment (MFNU) (Stray et al 2009b), although balance was not improved by stimulants (Bart et al 2006). Other studies similarly found that larger motor skills (as measured by the Test of Gross Motor Development-2) were less affected by stimulant medication treatment (Harvey et al 2007). …”
Section: Approaches To Motor Assessment In Adhdmentioning
confidence: 92%
“…Da mesma forma, Harvey et al (2007), ao investigarem os efeitos do Metilfenidato na atenção e nas habilidades de beisebol em 17 meninos, entre 7,8 a 9,9 anos de idade, utilizando um grupo controle e placebo para fins de comparação, concluíram que o Metilfenidato teve um efeito significativo sobre as medidas de atenção, mas não sobre as medidas de desempenho motor, demonstrando que as crianças com TDAH podem estar em risco de atraso no desenvolvimento das habilidades motoras fundamentais, já que todas as do respectivo grupo foram significativamente diferentes de seus pares sem o transtorno.…”
Section: Discussionunclassified
“…Estudos clínicos e epidemiológicos apontam que 30 a 50% das crianças com TDAH apresentam algum comprometimento da coordenação motora (POLATAJKO; CANTIN, 2005;MAGALHÃES;MISSIUNA;WONG, 2006;HARVEY et al, 2007;FLIERS et al, 2009;STRAY et al, 2009) o que acarreta déficits na execução das atividades de vida diária (FLIERS et al, 2010), na qualidade de vida, danos emocionais e sociais (MRUG et al, 2007).…”
Section: Introductionunclassified
“…95 Unmedicated girls with ADHD were also more likely to have more media time than their peers, which was associated with higher obesity rates. 95 Work has also found that relative to peers, children with ADHD have low gross motor performance, poor physical fitness, and delayed motor development 96 in addition to more negative feelings about physical activity. 97 Taken as a whole, these various results suggest that the link between ADHD and obesity is likely to be driven by both overeating and decreased physical activity, similar to obesity overall.…”
Section: The Association Between Adhd and Obesitymentioning
confidence: 99%